Biodiversity and enzymes bioprospection of Antarctic filamentous fungi - Martorell, María Martha; Ruberto, Lucas Adolfo Mauro; Fernandez, Pablo Marcelo; Castellanos, Lucia Ines; MacCormack, Walter P. (Antarctic Science)
Antarctica is one of the most suitable locations for the bioprospecting of psychrotrophic fungi, which play a key role in the nutrient cycle and organic material mineralization in cold environments. These actions mainly take place via the production of several cold-active extracellular enzymes. The aim of this study was to investigate the diversity of filamentous fungi from King George Island (25 De Mayo Island), Antarctica and their ability to produce extracellular hydrolytic enzymes at low temperatures. A total of 51 fungal isolates were obtained from 31 samples. Twelve genera were identified, with seven among the Ascomycota (Cadophora, Helotiales, Monographella, Oidodendron, Penicillium, Phialocephala, Phialophora, Phoma and Pseudogymnoascus), one Basidiomycota (Irpex) and two Mucoromycota (Mortierella and Mucor). Monographella lycopodina and Mucor zonatus, not previously reported in Antarctica, were identified. Nine isolates could not be identified to genus level and may represent novel species. Most of the studied fungi were psychrotrophic (76.5%). Nevertheless, only five isolates were able to grow at 35°C, 15°C being the optimal growth temperature for 65% of the fungal isolates. Results from enzyme production at low temperature revealed that the Antarctic environment contains metabolically diverse fungi, which represent potential tools for biotechnological applications in cold regions. Fil: Martorell, María Martha. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Ruberto, Lucas Adolfo Mauro. Universidad de Buenos Aires; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Houssay. Instituto de Nanobiotecnología. Universidad de Buenos Aires. Facultad de Farmacia y Bioquímica. Instituto de Nanobiotecnología; Argentina Fil: Fernandez, Pablo Marcelo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - ...